(untitled) (Global Journals of Research in Engineering, 2025)
This paper provides a foundational guide to establishing a chemical warehouse from ground up focusing on essential elements such as site selection regulatory compliance infrastructure safety protocols and operational workflows The aim is to present a concise practical introduction not only for engineers and project managers but also for warehousing companies logistics service providers and entrepreneurs planning to enter the chemical storage industry